Krep tekstüre teknolojisi - Alemdar, Serdar (Fen Bilimleri Enstitüsü, 1995)
Bu çalışmada incelenen krep tekstüre teknolojisi, sentetik bir lif olan polyesterden ipeksi özelliklere sahip iplikler üretilmesini amaçlamıştır. Düşük seviyede bir bire- iki büküm ve bunu takip eden bir yalancı büküm tekstüresinden oluşan krep tekstüre işlemiyle, krep ipek gibi yüksek bükümlü ipek ipliklerinin kendine özgü niteliklerini ve kumaşa ver_ dikleri pürüzlü tuşeyi düz polyester iplikleriyle elde etmek mümkün olmuştur. Büküm- tekstüre kombinasyonu sonucu iplik üzerinde oluşan bükümlü ve bükümsüz bölgelerin sağladığı krep etkisi, kumaşa ipek kumaşlara benzer pürüzlü bir yapı ve iyi bir kırışmazlık etkisi verir. Ayrıca düşük büküm ipliğin ve dolayısıyla kumaşın ipek gibi yumuşak olmasını sağlar. Tezin ilk bölümünde ipek ile suni ve sentetik lifler arasındaki ilişki gözden geçirilmiş, polyester ve ipek arasındaki benzerlikler belirtilmiş ve krep ipekten başlayarak krep tekstüreye kadar krep iplik elde etmek için uygulanan işlemlere değinilmiştir. Daha sonra ayrıntılı olarak bir krep tekstüre makinasının bölümleri ve krep tekstüre işleminin gelişimi anlatılmıştır. Ayrıca bir krep tekstüre makinasında işlem sırasında iplik üzerinde meydana gelen değişimler açıklanmıştır. Tezin deney bölümünde ise, krep tekstüre iplik imal eden işletmelerden temin edilen iplik numunelerinin Tekstil Laboratuvarı'nda ölçülen numara, mukavemet, ve büküm değerleri tablolar halinde gösterilmiştir. îpliğe krep etkisi veren bükümlü ve bükümsüz bölgelerin tespiti için S. E. M. (Scanning Electron Microscope) de çekilen iplik yüzey fotoğrafları ve krep tekstüre işlemi sonucu iplikteki filament kesitlerinde oluşan değişimi incelemek için mikroskopla çekilen iplik kesit fotoğrafları da bu bölümde yer almaktadır. Bundan başka krep tekstüre ipliklerin kumaş görünümünde meydana getirdiği değişimi görmek amacıyla iplik numunelerinden kumaş ördürülmüştür. Bu kumaşlar Ek A* da verilmiştir. Son bölümde ölçülen değerler ve elde edilen fotoğraflar değerlendirilmiş ve sonuçta krep tekstüre iplikler hakkındaki görüşler belirtilmiştir.

Crepe is the word for all the yarns having a particular reaction which gives a rough touch, a good anti-crease effect and at the same time a very appreciated handling to the fabrics. The crepe yarn, which is born with the processing of natural silk, was obtained through a very high twist level, over 2.000 tpm. Today, it is possible to get a crepe yarn with the polyester fibre by two ways. The first way is the conventional way which is similar to silk processing. The yarn is generally made in the range of 50-70-100 denier with the conventional number of filaments, around 2-2.5 DPF( denier per filaments) and is simply twisted on a two-for-one twister at 2.000-3.000 tpm and then steam set. It's made semi -dull for the imitation of well-known silk crepon. The second way is the crepe texturing process which is combining two-for-one twisting with false twist texturing. Thanks to polyester fibre's thermoplastic pecularity, we can have crepe yarns with a lower twist level followed by a texturing process. Crepe textured yarn is made also with 50- 70-100 denier polyester yarn but generally with a higher number of filaments than usual, around 1-1.5 DPF and with bright fibres. It's the best imitation of natural silk yarn with medium twist level. The twist level of yarn ranges from 600 to 1500 tpm. according to yarn count. Standart high twisted polyester yarns shrink alot under all the treatments they bear during the textile processing. This shrinkage reduces considerably its creping power, so that appreciable crepe effects can be obtained only with very open weaves. Some fibre producers have developed yarns with reduced shrinkage. These low shrinkage yarns with high twist develops higher creping power. By means of them we can obtain more creped fabrics like the crepons and crepe georgette. These yarns are generally sold as twisted yarns and are not available as flat yarns. Their price is higher in comparison with the standart twisted yarns. However, with the crepe texturing process, we can obtain high creping power from the standart flat polyester yarns as low shrinkage yarns. ix. About twenty years ago, crepe textured yarns was produced with a three-step intermittent process. These steps are twisting, steam-setting and pin texturing. The yarns, produced by this way, had good quality but total working time and production costs of the process were very high. Then, with the evolution of the crepe texturing machines, this procedure became an one-step continous process. The quality and the properties of the produced yarns are same but the one-step process is more economical than the other. The crepe texturing machines provide nearly %20 saving on the production costs. A crepe texturing machine consists of multiple, identical work stations and each one processing one composite thread. A work station has four main parts: _Two-for-one twisting unit _Heater unit _False twist texturing unit _Winding unit The two-for -one twisting unit is mainly formed by the two-for-one spindle. In the two-for-one twisting method, for every revolution of the spindle, two tours of twist is inserted to the yarn. This basic prenciple of two-for-one twist means the production will be two times greater. The spindle consists of the hollow spindle tube and the spindle disc. The feed bobbin is placed on this spindle disc. The yarn, unwinded from the bobbin, goes into the hollow tube and from the bottom of the disc, it takes-off to the yarn balloon which is rotating around the bobbin and enveloping it. The first twist is inserted to the yarn in the hollow tube, the second one is inserted in the yarn balloon. Because of the given twist, yarn contraction takes place and high tensions develop on the yarn. The heater units of the crepe texturing machines work according to the convection method. The yarn doesn't come into contact with the heated surface but is heated mainly by convection of hot air and partially by infra-red rays emitted by the heat source. The heater unit consists of heat- resistant ceramic or glass tubes. An electric coil laid on this tubes' exterior surface and maintains the air tempera_ ture inside the tubes at 100-250 CC. The tubes are enclosed in a box with a heat insulating material packed between the tubes and the box. The temperature in the heater is electronically controlled and this provides an accurate thermoregulation. The crepe texturing machines use magnetic-pin spindle type false twist texturing units. This units consists of the twist tube and the pin inside it. The yarn, passing through the twist tube, wraps round the pin and rotates. On each side of the twist tube, equal amounts of twist in opposite directions is inserted to the yarn. The sum of twist throughout the length of the yarn as a whole is zero. The twist below the twist tube is heat-set and after the yarn passed through the tube, it becomes untwisted because of the twist given in the opposite direction. But as a result of molecular deformation of yarn structure in the heat-setting, the yarn gains bulkiness, stretch and torque. The winding unit consists of the take-up bobbin drive, the cradle and the traverse guide. A cylindrical friction roller drives the bobbin and determines the winding speed. High frictional forces are exerted between the yarn and the roller by the elastomeric cover on the roller. The cradle of the winding unit clamps the crepe textured yarn carrier, establishes the proper inclination for conical winding and exerts appropriate winding pressure. The traverse guide provide the regular setting of yarns on the take-up bobbin. In crepe textured machines, centrally driven traverse guides are used to build random cross-wound bobbins. Besides these main parts, other important units of the crepe texturing machine are two independent overfeed devices, one within two-for-one spindle and the heater, the second one is within false twist spindle and winding unit. Their main function is reducing the yarn tension to a suitable level for texturing and winding processes. An overfeed device is formed by a wear-resistant ceramic, grooved wheel. The tan_ gential speed of this wheel is more than yarn speed so it delivers more yarn than usual to the subsequent process zone. By this way, the yarn tension and shrinkage is controlled. In this study, the crepe texturing process is examined in 521 DFT model of RATTI Crepetext machine. This machine consists of nine sections. In every section there are ten spindles, five in front and five in backward, and a heater which is build up as a single block with ten thread passes. Headstocks, placed in each side of the machine, houses the main motor, gear-boxes of driven units and the heater temperature control unit. The spindle is driven from the main motor by a tangential belt laid along the machine. A pulley, mounted to the motor, delivers the motion to the tangential belt. For adjusting the spindle rotation speed and the twist level, this pulley's diameter is changed. Other movable machine parts are also driven by the main motor with the help of gear mechanisms. xx In the beginning of crepe texturing process, standart flat feed yarn is twisted on two-for-one spindle and a real twist between 600-1500 tpm. is inserted. In texturing zone, within the first overfeed device and false twist spindle, a false twist, approximately three times more than real twist, is inserted to the yarn in the opposite direction. So, firstly the yarn is untwisted and then twisted again in opposite twist direction. This new twist is heat-set in the heater and the cooling zone within the heater and the false twist spindle. The yarn passes through the false twist spindle. Between the spindle and the second overfeed device, the false twist of the yarn is untwisted and the yarns regains its real twist But, because of the molecular change occured in the filaments during the heat-setting, the filaments tend to turn their heat-set structure. This reaction exerts torsional forces on the yarn. By the effect of these torsional forces, the twist of the yarn is pressed, pushed along the yarn and gathers at random points. This event causes the formation of twisted and untwisted (bulky) regions on the yarn. Thus, the yarn has a thin-thick effect which is known as "pebble effect". The fabrics, formed by these yarns, have a rough handling like silk crepe fabrics because of this yarn formation. After this creping zone, the yarn reaches to the second overfeed device and the high yarn tension is lowered for prosecuring optimum bobbin density in the winding process. In the winding unit, the yarn is delivered to the cross wound take-up bobbins. In the experimental part of the study, at first, samples of crepe textured yarns and their feed yarns in different deniers and filament numbers are obtained from crepe textured yarn producers. These yarns' yarn count, twist amount, break strength and elongation values are measured at the Textile Laboratory. Then, with S.E.M. (Scanning Electron Microscope) the crepe textured yarn samples' surface photographs are taken for determining twisted-untwisted regions of the yarn. Using a microscope, the deformations of the yarn cross- sections after the crepe texturing process is examined with different methods and cross-sectional microphotographs of the yarn samples are also taken. Furthermore, using feed and crepe textured yarns, some knitted fabrics are made in a circular knitting machine and the differences of the fabric surfaces are noticed. XXI As a result of these experiments, the special properties that the yarn gains in crepe texturing process, are shown. The yarn gets strength in spite of the deformations of its cross-section and a twisted-untwisted structure which gives the crepe effect to the fabrics. This can be seen on the knitted fabric samples given in Ek A. The fabrics made from feed yarns have flat, ordinary surfaces but the fabrics made from crepe textured yarns have a rough touch and silk-like appearence.
Crepe texturing technology
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: krep tekstüre; crepe texturing